2003
DOI: 10.1038/sj.bjc.6601138
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose, chemotherapy, hormonal treatment and risk of second cancer after breast cancer treatment

Abstract: In total, 281 of the 7711 women who were initially treated for breast cancer between 1954 and 1983 at the Gustave Roussy Institute developed a second malignant neoplasm (SMN) other than second primary breast cancer and nonmelanoma skin cancer at least 1 year after breast cancer treatment. We carried out a nested case -control study to determine the overall relationship between the dose of radiotherapy received at a given anatomical site and the risk of SMN at the same site. In total, 75% of the cases of SMN we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 24 publications
0
58
0
11
Order By: Relevance
“…A number of previous studies have demonstrated a link between hormonal treatment for invasive breast cancer and the development of uterine or endometrial cancer (Khandekar et al, 1978;Hardell, 1988;Fornander et al, 1989;Atlante et al, 1990;Gusberg, 1990;Mathew et al, 1990;Andersson et al, 1991;Fisher et al, 1994;Rubino et al, 2003). However, it is generally accepted that for women with invasive breast cancer, the benefits of hormonal treatment, such as tamoxifen, outweigh the associated risks (Gail et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…A number of previous studies have demonstrated a link between hormonal treatment for invasive breast cancer and the development of uterine or endometrial cancer (Khandekar et al, 1978;Hardell, 1988;Fornander et al, 1989;Atlante et al, 1990;Gusberg, 1990;Mathew et al, 1990;Andersson et al, 1991;Fisher et al, 1994;Rubino et al, 2003). However, it is generally accepted that for women with invasive breast cancer, the benefits of hormonal treatment, such as tamoxifen, outweigh the associated risks (Gail et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Women with previous breast cancer are known to carry a two-fold increased risk of second cancer in comparison to the general population (Rubino et al, 2003;Soerjomataram et al, 2005a). Studies assessing the risk of second cancer following the diagnosis of BCIS (breast carcinoma in situ) are however scarce or only focused on the risk of second breast cancer (Habel et al, 1997;Warnberg et al, 2000;Claus et al, 2003;Levi et al, 2005;Rawal et al, 2005).…”
mentioning
confidence: 99%
“…These findings have been attributed to shared lifestyle and genetic risk factors, carcinogenic effect of treatment (in particular radiotherapy), and most commonly to better medical surveillance of women with previous breast cancer. Most of those studies addressing melanoma risk after breast cancer concerned patients treated in the distant past and therefore with treatment regimens not including hormonal therapy (15,16), or lacked antiestrogen data or when available, did not evaluate if hormonal therapy influenced melanoma risk (17,19,(20)(21)(22)24). To our knowledge, only 2 prior studies evaluated melanoma cancer risk among breast cancer patients according to hormonal therapy (23,24).…”
Section: Discussionmentioning
confidence: 91%
“…Most of those studies addressing melanoma risk after breast cancer concerned patients treated in the distant past and therefore with treatment regimens not including hormonal therapy (15,16), or lacked antiestrogen data or when available, did not evaluate if hormonal therapy influenced melanoma risk (17,19,(20)(21)(22)24). To our knowledge, only 2 prior studies evaluated melanoma cancer risk among breast cancer patients according to hormonal therapy (23,24). The large study from the Netherlands of a population-based breast cancer cohort (23) showed an increased risk of secondary melanoma (SIR: 1.69, 95% CI: 1.44-1.97).…”
Section: Discussionmentioning
confidence: 99%